2022
DOI: 10.1002/wsb.1340
|View full text |Cite
|
Sign up to set email alerts
|

A Sonic Net deters European starlings Sturnus vulgaris from maize silage stores

Abstract: Deterrents against avian pest species might be more effective if they were based on some aspect of the target species' sensory salience. Sonic Nets broadcast a loud and spatiallyfocused pink noise that spans the frequency range of the target species' vocalizations, restricting interspecific communication so that it is costly for birds to remain in the treated area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…As such, broadcasting hawk vocalizations or the Sonic Net during the late-season when blackbirds are still residing in nesting habitat could reduce abundances and potentially mitigate crop damage (sensu Tracey et al 2007). Other studies have demonstrated that the Sonic Net can reduce problematic bird abundances in target areas (Swaddle et al 2016, Werrell et al 2021, Woods et al 2022, with similar studies in agricultural settings showing even greater reducing effects than we found (Woods et al 2022).…”
Section: Comparisonsupporting
confidence: 86%
See 3 more Smart Citations
“…As such, broadcasting hawk vocalizations or the Sonic Net during the late-season when blackbirds are still residing in nesting habitat could reduce abundances and potentially mitigate crop damage (sensu Tracey et al 2007). Other studies have demonstrated that the Sonic Net can reduce problematic bird abundances in target areas (Swaddle et al 2016, Werrell et al 2021, Woods et al 2022, with similar studies in agricultural settings showing even greater reducing effects than we found (Woods et al 2022).…”
Section: Comparisonsupporting
confidence: 86%
“…First, we noted if blackbirds were detected in fields or in nesting habitat, but due to low sample sizes we could not statistically evaluate if our treatments reduced numbers in agricultural fields specifically. Second, because our Sonic Net playback design was quieter than previous studies (Swaddle et al 2016, Werrell et al 2021, Woods et al 2022, our data may not be directly comparable to previous studies on the Sonic Net. However, even when broadcast at a quieter volume, the Sonic Net still reduced late-season blackbird abundances.…”
Section: Comparisonmentioning
confidence: 59%
See 2 more Smart Citations